2012
DOI: 10.3168/jds.2011-5170
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social contact and milk allowance on responses to handling, play, and social behavior in young dairy calves

Abstract: The aim of this study was to investigate the effects of social contact and milk allowance on social behavior, play behavior, and responses to handling in dairy calves. Forty test calves and 16 companion calves were allocated to 1 of 5 treatments from birth to 4 wk of age: (1) housed singly and fed 5 L of milk/d; (2) housed singly and fed 9 L of milk/d; (3) housed in pairs and fed 5 L of milk/d; (4) housed in pairs and fed 9 L of milk/d; or (5) kept with the dam and fed 9 L of milk/d. From 4 to 6 wk of age, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 36 publications
6
69
1
5
Order By: Relevance
“…Early separation is often perceived to be unnatural and problematic for the welfare of the cow and calf (Ventura et al, 2013), and research has shown that nursing can provide health and welfare benefits (Krohn, 2001;Flower and Weary, 2003). For example, calves reared with the dam stand earlier after birth (Lidfors, 1996), gain more weight than calves reared artificially with restricted milk allowances (Flower and Weary, 2001) and show reduced signs of distress during an isolation test (Duve et al, 2012). Long-term positive effects of staying longer with the cow can be seen when heifers are introduced into the dairy herd (Wagner et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Early separation is often perceived to be unnatural and problematic for the welfare of the cow and calf (Ventura et al, 2013), and research has shown that nursing can provide health and welfare benefits (Krohn, 2001;Flower and Weary, 2003). For example, calves reared with the dam stand earlier after birth (Lidfors, 1996), gain more weight than calves reared artificially with restricted milk allowances (Flower and Weary, 2001) and show reduced signs of distress during an isolation test (Duve et al, 2012). Long-term positive effects of staying longer with the cow can be seen when heifers are introduced into the dairy herd (Wagner et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Spel manifesteert zich onder meer als springen, schoppen en rennen, schijnvechten (Reinhardt 1980), en manipulaties van objecten (Brownlee 1954). Spelgedrag is niet noodzakelijk om te overleven en in suboptimale omstandigheden wordt dit gedrag verminderd of zelfs achterwege gelaten; spelgedrag van kalveren neemt bijvoorbeeld af als het voeraanbod afneemt (Duve et al, 2012) of als de kalveren aan pijnlijke procedures onderworpen worden (Mintline et al, 2013). …”
Section: Spelgedragunclassified
“…Early social environment influences the development of social behaviour, impacting social hierarchy later in life (Warnick et al 1977) and response to competition (Duve et al 2012) or a novel environment (De Paula Vieira et al 2012). For example, Duve et al (2012) reported that calves reared with social contact (pair-housing) accessed feed more successfully in a competitive challenge than calves reared in individual pens.…”
Section: Social Environmentmentioning
confidence: 99%
“…For example, Duve et al (2012) reported that calves reared with social contact (pair-housing) accessed feed more successfully in a competitive challenge than calves reared in individual pens. There is also evidence that differences in meal patterns developed in response to early environment may persist when mediated by different social factors, such as degree of competition.…”
Section: Social Environmentmentioning
confidence: 99%